Saluran Islamisasi di Palembang - APRIANA APRIANA; HERYATI HERYATI; NURHAYATI DINA; HUDAIDAH HUDAIDAH (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2022)
Researchers in this study raise issues regarding channels of Islamization in South Sumatra. The method used is the historical method. Including the type of research library research. Data collection was obtained through a literature study by looking for references related to this research. After the data has been collected, an analysis is carried out including the stages of verification, interpretation and historiography. The results of this study indicate that Islamization channels in the South Sumatra region, especially Palembang, include: trade, marriage, Sufism, politics and education. Trade is the channel of the earliest Islamization carried out. This was very possible because along with the busy trade traffic in Palembang from the 7th to the 16th century AD, so that there were marriages between Muslim merchants and local residents. The next channel of Islamization in Palembang is through Sufism. Sufism in Palembang is also a media that plays a role in shaping the social life of Palembang people. This is proven by the existence of texts of Sufism teachings. In the political field, the Islamization of the power elite occurred, where marriages between Arabs and the children of local authorities took place for political purposes. Meanwhile, in the field of education during the Palembang Darussalam Sultanate, Islamic development occurred in the field of science. As a center for the study of religion and literature, the activities of religious studies are quite developed and advanced. Religious educational institutions are managed by religious bureaucrats through recitation at mosques and at the homes of religious officials. Therefore, in Palembang there were no pesantren like in Java